Cloning and identification of Bartonella α-enolase as a plasminogen-binding protein. (October 2019) - Deng, Hongkuan; Wu, Suge; Song, Qian; Zhang, Junshi; Sang, Feng; Sun, Xiaoyue; Xu, Tong; Gao, Yan; Zhao, Bosheng
Abstract: Bartonella infection is distributed worldwide with animal and public health. Recent studies have shown that host cells infection by Bartonella has a series of different infection stages, beginning with encounter and adherence to the cells. In this study, we expressed and purified recombinant Bartonella henselae ( B. henselae ) α-enolase. And we found that B. henselae α-enolase is highly conserved in Bartonella species . The interacting protein partners of B. henselae α-enolase were showed by String-11. The interactions between B. henselae α-enolase and human plasminogen were subsequently confirmed by ELISA, pull down, T7 phage display and molecular docking assays. And the plasminogen-binding sites of B. henselae α-enolase are predicted at 247 FYKNGSYFY 255 . These findings will help elucidate and improve the understanding of the molecular mechanisms of Bartonella infection. Highlights: B. henselae α-enolase is highly conserved in Bartonella species. B. henselae α-enolase is able to bind to human plasminogen. B. henselae α-enolase plasminogen-binding sites are predicted at 247 FYKNGSYFY 255 .